2020
DOI: 10.1016/j.heliyon.2020.e05695
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social networking sites usage and psychological distress among undergraduate students during COVID-19 lockdown

Abstract: During the outbreak of the COVID-19 pandemic, interpersonal interactions are restricted to social networks. Undergraduate students are isolated in their homes and dorms. Loneliness is closely related to psychological distress. Fear of contracting the disease will worsen psychological distress. The purpose of this study was to assess the severity of depression, anxiety, and stress symptoms among undergraduate students and their relationships with social networking sites usage during the COVID-19 lockdown. An on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 27 publications
3
37
0
7
Order By: Relevance
“…Finally, studies conducted by Al-Dwaikat, Aldalaykeh, and Rababa (2020) and Al-Tammemi et al (2020) in Jordan, Hamza, Ewing, Heath, andGoldstein (2021) in Canada, andHunt et al (2021) in the U.S. all indicated that students experienced psychological distress during the pandemic period, all of which are consistent with the result of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, studies conducted by Al-Dwaikat, Aldalaykeh, and Rababa (2020) and Al-Tammemi et al (2020) in Jordan, Hamza, Ewing, Heath, andGoldstein (2021) in Canada, andHunt et al (2021) in the U.S. all indicated that students experienced psychological distress during the pandemic period, all of which are consistent with the result of this study.…”
Section: Discussionsupporting
confidence: 88%
“…For example, a web-based cross-sectional survey of 476 university students living in Bangladesh utilizing the Patient Health Questionnaire (PHQ-9) and Generalized Anxiety Disorder (GAD-7) found that 82.4% of students have mild to severe depressive symptoms, and 87.7% of students have mild to severe anxiety symptoms (32). In Jordan, an online survey conducted in April 2020 involved 456 undergraduate students utilizing the DASS-21 who reported that the majority of students had symptoms of depression (74.1%), anxiety (59.6%), and stress (61.2%) (33). Another study that involved 2,086 college students regarding the impact of COVID-19 on their mental health in April 2020 found that 91% of the participants had anxiety or stress symptoms (34).…”
Section: Discussionmentioning
confidence: 99%
“…The anxiety subscale consists of items 2, 4, 7, 9, 15, 19, and 20, with scores ranging from normal (0-7), mild (8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), to extremely severe (20+). Finally, the stress subscale consists of items 1, 6, 8, 11, 12, 14, and 18, with scores ranging from normal (0-14), mild (15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33), to extremely severe (34+). The DASS-21 is a reliable, easy-to-use screening instrument and has been wellreceived globally.…”
Section: Depression Anxiety and Stress Scalesmentioning
confidence: 99%
“…All this caused greater anxiety and a general demotivation in students, aspects that have been analysed in other works (Aristovnik et al, 2020 ; Mertens et al, 2020 ). In addition, a withdrawal of students with respect to social relations with their environment was identified (Al‐Dwaikat et al, 2020 ), which in many cases led to problems of anxiety, stress, isolation and loneliness (Tull et al, 2020 ; Unger & Meiran, 2020 ). Similarly, lockdown has led to students, along with the rest of the population, facing limited mobility.…”
Section: Covid‐19 and Its Impact On University Educationmentioning
confidence: 99%